Fully Endoscopic Resection of Pineal Region Tumors - Shahinian, Hrayr (Georg Thieme Verlag KG, 2013)
Background and Objective Surgical treatment for pineal tumors is technically challenging—weighing the risks and benefits of microsurgical resection for the patient with a pineal tumor versus settling for an endoscopic third ventriculostomy and biopsy is sometimes difficult. Traditional microsurgical resection for pineal region tumors has typically required large open craniotomies and involvement or retraction of neural tissue with significant mortality and morbidity. With the advancement of high-resolution fiber optics, a fully endoscopic, supracerebellar, infratentorial approach, without any cerebellar retraction or manipulation of neural tissue, is introduced for the gross total resection of pineal region tumors. Conclusion As an endoscopic modification of the open craniotomy procedure, this technique combines the advantages and benefits of both open microsurgical resection and minimally invasive endoscopic surgeries.